Modular System of Cabinets for Mass-Customized Furniture - S'harin Mokhtar; Cai Xifeng; Zhou Wenming (Environment-Behaviour Proceedings Journal, 2025)
To support the establishment of modular systems for Mass Customization furniture enterprises, cabinet products are used as research objects to establish a modular system for cabinet products suitable for medium-sized enterprises. It is proposed to classify cabinet products according to structural characteristics and divide cabinet products into cabinets, tables, and special function categories based on the principles of standard structure, replicability, and reusability. A Mass Customization furniture production method is established in which a combination of unit modules is composed of a combination of furniture. Then panels and accessories are selected to form the final furniture combination model.